Pityriasis Rubra Pilaris With Extensive Follicular Acantholysis Resembling Pemphigus Vulgaris: A Case Report. (January 2019) - Lilo, Mohammed T.; Yan, Shaofeng; Chapman, Michael Shane; Linos, Konstantinos
Abstract : Abstract: Pityriasis rubra pilaris (PRP) is a rare, chronic, heterogeneous, papulosquamous inflammatory dermatosis of unknown etiology. Although erythematous scaly patches characterize the classic presentation of PRP, a broad range of clinical presentations has been reported. Histologically, PRP is characterized by psoriasiform acanthosis with alternating orthokeratosis and parakeratosis and rarely small acantholytic foci. In this article, we report a patient who presented with diffuse erythroderma and extensive acantholysis mimicking pemphigus vulgaris histologically.